Perinatal exposure to androgen excess and the effects on the rat uterine estradiol responsiveness - Guerra, Marina T. [UNESP]; Sanabria, Marciana [UNESP]; Petrusz, Peter; Kempinas, Wilma de Grava [UNESP] (Wiley-Blackwell, 2015)
Androgen exposure during sexual development induces alterations in steroidal target tissues. The objective of this study was to evaluate the uterine responsiveness to estradiol after perinatal androgenization. Pregnant Wistar rats were exposed to corn oil or testosterone propionate at 0.05, 0.1, or 0.2 mg/kg from gestational day 12 until postnatal day 21. Female offspring was challenged with estradiol (E2 ) after weaning (0.4 mg/kg) and at adulthood (10 or 100 µg/day), when the pituitary response was also evaluated. At adulthood, control and 0.05 mg/kg groups presented a uterine weight increment when exposed to 100 µg/day of E2 , 0.1 mg/kg group only responded to 10 µg/day of E2 , and the 0.2 mg/kg group showed increased uterine weight at both doses. The pituitary weight was similarly increased after estradiol stimulation in all experimental groups. In conclusion, testosterone propionate exposure induced an abnormal stimulation of uterine tissue growth by estrogen stimulus without affecting pituitary response. More studies are needed to clarify whether these alterations are capable of impairing the reproductive capacity of the female tract. © 2015 Wiley Periodicals, Inc. Environ Toxicol, 2015.
Keywords: Androgen; Estradiol; Offspring; Uterus response